The induction of intercellular adhesion molecule 1 (ICAM-1) expression on human fetal astrocytes by interferon-gamma, tumor necrosis factor alpha, lymphotoxin, and interleukin-1: relevance to intracerebral antigen presentation. - Frohman, E; Frohman, T; Dustin, M; Vayuvegula, B; Choi, B; Gupta, A; van den Noort, S; Gupta, S (1989)
Antigen presentation reactions are dependent upon the expression of the class II major histocompatibility antigens (MHC), the T-cell receptor, and the presented antigen. Recent studies demonstrate that such processes also require the presence of adhesion molecules such as lymphocyte functional antigen 1 (LFA-1) and its cell surface ligand, intercellular adhesion molecule 1 (ICAM-1). It has been suggested that the brain astrocyte can function as a facultative antigen presenting cell (APC). This hypothesis is based upon the ability to induce the expression of the class II MHC antigens on astrocytes, and on their ability to present myelin basic protein to encephalitogenic T-cells in vitro. The best in vivo data showing that astrocytes serve as intracerebral APCs is the finding that astrocytes in multiple sclerosis plaques are DR+ (class II MHC in human). However, it still remains to be resolved whether the in vivo expression of the MHC antigens in disease states is instrumental to antigen presentation mechanisms or whether these cell surface glycoproteins are expressed secondary to brain immune responses. If astrocytes function as immunocompetent APCs within the brain, it would seem that they would also be able to express molecules important for intercellular adhesion. Here, we present the first data that indicates that human astrocytes are capable of expressing ICAM-1 in response to cytokines that either induce or upregulate the expression of DR. In essence, cytokines derived from different cell types seem to exert similar pleiotropic effects on the modulation of MHC and ICAM-1 expression on astrocytes.(ABSTRACT TRUNCATED AT 250 WORDS)